Peran Media Massa dalam Sekuritisasi Pandemi Covid-19 di Indonesia - Angga Nurdin Rachmat (Intermestic: Journal of International Studies, 2023)
The highly contagious nature of COVID-19 and the absence of standard medical therapy to treat the infection require a treatment that focuses on changing people's behavior patterns. In the Indonesian context, the policies implemented in dealing with the COVID-19 pandemic were implemented by carrying out extraordinary measure policies as part of the symptom of placing the pandemic as a security threat to the state and society through a securitization process. The securitization process against COVID-19 in Indonesia will involve various actors both related to securitizing actors and functional actors, which in this study will raise the role of functional actors namely the mass media in the securitization process. Therefore, this research will discuss the role of the mass media in the process of securitizing the COVID-19 pandemic in Indonesia? This research is based on the securitization theory developed by experts at the Coppenhagen School by trying to develop the role of functional actors in the securitization process on health issues by taking a study on the COVID-19 Pandemic in Indonesia. This study found that the mass media has the characteristics of a functional actor as stated by Floyd (2020) in the securitization of the COVID-19 pandemic in Indonesia. Meanwhile, the role of the mass media takes three roles in the process of securitizing the COVID-19 pandemic in Indonesia as stated by Hass (2009), namely as a forum for existence for actors, the mechanism of securitizing actors starts speech acts and builds and maintains situations.